PENGARUH PENGUASAAN KOSAKATA TERHADAP KETERAMPILAN MEMBACA KRITIS - Sakaria Sakaria; Asia M (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the effect of vocabulary mastery on critical reading skills. The relationship between vocabulary mastery as a predictor and critical reading skills as a criterion was investigated in this study using correlational methodology. The research sample consisted of 30 fourth-semester students in the academic year 2024/2025 who were enrolled in the Indonesian Language and Literature Education Study Program at Makassar State University. Data collection was carried out using vocabulary mastery instruments and critical reading tests. The research data were analyzed using SPSS version 30 with descriptive and inferential statistical methods. The results showed that vocabulary mastery had a significant influence on students' critical reading skills. The ability to interpret reading texts is strongly influenced by vocabulary understanding, which serves as a tool for readers to understand the meaning of words in improving the ability to analyze and infer reading texts. In addition, good vocabulary mastery supports readers in evaluating the text and understanding the implied meaning, which is essential in the critical reading process. The results of this study confirm the importance of vocabulary mastery in reading learning, especially in terms of improving critical reading skills.